PENGEMBANGAN E-BOOK INTERAKTIF TEKS CERITA FANTASI BERBASIS PROJECT-BASED LEARNING (PjBL) BERBANTUAN KOMIK DIGITAL SISWA KELAS VII SMP NEGERI 7 PADANG - Fitri, Hasnah; Indriyani, Vivi; Abdurahman; Syafrina, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop an interactive e-book on fantasy story texts based on Project-Based Learning (PjBL) assisted by digital comics for Grade VII students of SMP Negeri 7 Padang, and to describe the validity and practicality levels. The research employed the Research and Development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Product validation was conducted by material and media experts, while practicality was measured through teacher and student response questionnaires. The results of material expert validation showed a percentage of 87.67% (Very Valid), and student practicality results reached 88.33% (Very Practical). The findings indicate that the developed interactive e-book meets quality standards and is suitable for implementation in fantasy story text learning. The integration of PjBL and digital comics has proven capable of increasing student learning motivation and active engagement in understanding fantasy story text material.